Obesity induced gut dysbiosis contributes to disease severity in an animal model of multiple sclerosis - Shahi, Shailesh K.; Ghimire, Sudeep; Lehman, Peter; Mangalam, Ashutosh K. (Frontiers in Immunology, 2022)
Background: Multiple sclerosis (MS) is an inflammatory and demyelinating disease of the CNS. The etiology of MS is complex, results from the interaction of multiple environmental and genetic factors. Although human leukocyte antigen-HLA alleles such as HLA-DR2 and –DR3 are considered the strongest genetic factors, the environmental factors responsible for disease predisposition are not well understood. Recently, diet and gut dysbiosis have emerged as an important environmental factor linked to the increased incidence of MS. Especially, western diets rich in protein and fat have been linked to the increased incidence of obesity. Numerous clinical data indicate a role of obesity and gut dysbiosis in MS; however, the mechanistic link between gut microbiota and obesity in the pathobiology of MS remains unclear. Present study determining the mechanisms driving MS severity in the context of obesity utilizing a high-fat diet (HFD) induced obese HLA-DR3 class-II transgenic mouse model of MS. Methods: HLA-DR3 transgenic mice were kept on a standard HFD diet or Normal Chow (NC) for eight weeks. Gut microbiota composition and functional analysis were performed from the fecal DNA of mice. Experimental autoimmune encephalomyelitis-EAE (an animal model of MS) was induced by immunization with the proteolipid protein-PLP91-110 peptide in complete Freud’s Adjuvant (CFA) and pertussis toxin. Results: We observed that HFD-induced obesity caused gut dysbiosis and severe disease compared to mice on NC. Amelioration of disease severity in mice depleted of gut microbiota suggested an important role of gut bacteria in severe EAE in obese mice. Fecal microbiota analysis in HFD mice shows gut microbiota alterations with an increase in the abundance of Proteobacteria and Desulfovibrionaceae bacteria and modulation of various bacterial metabolic pathways including bacterial hydrogen sulfide biosynthetic pathways. Finally, mice on HFD showed increased gut permeability and systemic inflammation suggesting a role gut barrier modulation in obesity induced disease severity. Conclusions: This study provides evidence for the involvement of the gut microbiome and associated metabolic pathways plus leaky gut in obesity-induced modulation of EAE disease severity. A better understanding of the same will be helpful to identify novel therapeutic targets to reduce disease severity in obese MS patients.